The interference of the Catholic Church in the extension of sexual and reproductive rights in Chile. The case of the partial decriminalisation of abortion in 2017 - Puraye, Alix (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2021)
In Chile, the issue of sexual and reproductive rights —unthinkable for a long time under a dictatorship characterised by structural machismo— began to arise in the 1990s, in a democracy still marked by the remnants of the former authoritarian regime. The expansion of these rights is still strongly hampered today by a historically decisive actor in the country's political life: the Catholic Church. Relying on a heterogeneous set of actors, it has carried out a very effective rhetorical and militant strategy to delay the feminist agenda by restricting as much as possible the enactment of laws that interfere with its essentialist conception of women and the family. The case of the partial decriminalisation of abortion in 2017 is archetypal to the extent that the political character of feminist arguments in favour of women's autonomy —and of their bodies— clashes with the moral doctrine of the Church, which sees abortion as the embodiment of the "gender ideology" and the "culture of death".